Cancer risk in HIV-infected individuals on HAART is largely attributed to oncogenic infections and state of immunocompetence - Vogel M (European Journal of Medical Research, 2011)
Abstract Objectives To estimate the cancer risk of HIV-infected patients in the HAART era with respect to a general reference population and to determine risk factors for malignancy. Methods Long term (1996-2009) cancer incidence of the Bonn single centre HIV cohort was compared to the incidence of the reference population of Saarland using standardized incidence ratios (SIR). Poisson regression analysis was used to identify predictors of cancer risk. Results 1,476 patients entered the cohort, enabling 8,772 person years of observation. 121 tumours in 114 patients, 7 in-situ and 114 invasive cancers, were identified. Malignancies associated with infectious agents such as Kaposi sarcoma (SIRs: male: 5,683; female: 277), non-Hodgkin lymphoma (SIRs male: 35; female: 18), anal cancer (SIRs male: 88; female: 115) as well a cervical carcinoma (SIR female: 4) and Hodgkin's disease (SIR male: 39) and liver cancer (SIR male: 18) were substantially more frequent in HIV-infected patients than in the general population (p < 0.001, each), whereas all other types of cancer were not increased. Poisson regression identified HAART (incidence rate ratio IRR (95% CI): 0.28 (0.19-0.41), p < 0.001), CD4 count (IRR per 100 cells/μl increase: 0.66 (0.57-0.76), p < 0.001), hepatitis B (IRR: 2.15 (1.10-4.20), p = 0.046) and age (IRR per 10 year increase: 1.23 (1.03 - 1.46), p = 0.023) as independent predictors for the occurrence of any type of cancer. Conclusions HAART and preserved CD4 cells preferentially reduce the risk of malignancies associated with oncogenic infections.